Characteristics of Concrete Exposure in the Marine Environment - Abdul Rahim, Mustaqqim; Amri, Nur Adlina; Mohamad Ibrahim, Norlia; Ayob, Afizah; Salehuddin, Shamshinar; Rahim, Nur Liza; Shahidan, Shahiron (International Journal of Integrated Engineering, 2024)
The characteristics of concrete in the marine environment with various grades of concrete of grade 30, 35, and 40 investigate in this research. The objective of this study is to identify the optimum grade of concrete in the marine environment. Several test was conducted such as water absorption, density, ultrasonic pulse velocity (UPV), and compressive strength. The results show that the optimum grade of concrete in the marine environment is grade 40, which has the lowest water absorption of 8%, the highest density test of 2399 kg/m3, the highest UPV test result of 4723.249 m/s, and the highest compressive strength test of 31.63 MPa. The high result indicates the high quality and durability of the concrete. The study contributes to the understanding of the characteristics of concrete in the marine environment and provides valuable information for the selection of the appropriate grade of concrete for marine structures.